Filled Skutterudites for Broadband Saturable Absorbers - Lee, Junsu; Yu, Byung-Kyu; Jhon, Young In; Koo, Joonhoi; Kim, Sung Jin; Jhon, Young Min; Lee, Ju Han (WILEY-V C H VERLAG GMBH, 2017)
Filled skutterudites (FSs), which are known to be good thermoelectric materials, have been intensively investigated in the field of condensed matter physics in the past decades, due to their large variety of electronic and magnetic properties. However, to the best of the authors' knowledge, there has been no previous investigation of the optical properties of FSs. The nonlinear optical saturable absorption property of FSs is investigated in this work for the first time, and the results are reported here. More specifically, Co4Sb12 is chosen as a binary skutterudite system, and indium ions are added as a filling element to form a FS of In0.2Co4Sb12. The material properties are systematically investigated using a series of measurements. Density functional theory calculations of the electronic band structures of InCo4Sb12 and In0.25Co4Sb12 are conducted for better understanding of their energy band structures. It is also demonstrated that a broadband saturable absorber (SA) that can simultaneously operate at 1.5 and 1.9 mu m can readily be implemented by depositing particles of In0.2Co4Sb12 onto fiber ferrules. The efficacy of the prepared SA is tested by incorporating the device into rare earth ion-doped fiber ring cavities, to show its capability for both 1.5 and 1.9 mu m operation.
Keywords: DOPED FIBER LASER; EVANESCENT FIELD INTERACTION; MOLYBDENUM-DISULFIDE MOS2; THERMOELECTRIC PROPERTIES; MODE-LOCKING; PULSE LASER; TOPOLOGICAL INSULATOR; PHOTONIC APPLICATIONS; TRANSPORT-PROPERTIES; BLACK PHOSPHORUS